Self-care practices performed by patients with type 2 diabetes mellitus in Cartagena- Colombia, 2021 - Madero Zambrano, Kendy Paola; Orgulloso Bautista, Claudia Alejandra (Revista Cuidarte, 2022)
Introduction: Diabetes is a chronic disease that can cause physical disability due to various multiorgan complications. Self-care practices are essential for health maintenance and prevention of these complications. Objective: To analyze the self-care practices performed by patients with type 2 diabetes mellitus in Cartagena in 2021. Materials and Methods: An observational, analytical, crosssectional study was conducted on 100 patients with type 2 diabetes mellitus. A questionnaire (sociodemographics, patients’ medical background, and self-care practices) was used for univariate, bivariate, and multivariate analysis, and logistic regression analysis. Results: Most patients had a 1-to-5-year diagnosis of diabetes (33%) and blood glucose ≥140 mg/dl (40%). There were hygiene (66%), diet (60%), and sleep (50%) good practices, but low physical activity (61%). Self-care practices were significantly associated with physical activity risk and not having school or primary education (OR: 15.44; 95% CI 2.78-85.48). They are a dietary protector, when aged between 41 and 56 years (OR: 0.07; 95% CI 0.00-0.60), 52 and 72 years (OR: 0.04; 95% CI 0.00-0.42) and older than 73 years (OR: 0.01; 95% CI 0.00-0.28). Discussion: The population had a good level of self-care practices. It is consistent with what was observed by other authors; which determined that a large part of the sample had a high level of general knowledge about self-care. Conclusions: The self-care practices carried out by patients with type 2 diabetes mellitus are generally good in terms of hygiene, diet and sleep, and poor in terms of physical activity.How to cite this article: Madero Zambrano Kendy Paola, Orgulloso Bautista Claudia Alejandra. Prácticas de autocuidado que realizan pacientes con diabetes mellitus tipo 2 de Cartagena, Colombia. 2021. Revista Cuidarte. 2022; 13(3): e2534. http://dx.doi.org/10.15649/cuidarte.2534
Keywords: Diabetes Mellitus; Self-Care; Habits